Thin-Film Nanocomposite Reverse Osmosis Membrane with High Flux and Antifouling Performance via Incorporating Maleic Anhydride-Grafted Graphene Oxide - Zhongyan Chen; Boqun Zhao; Yuhang Qin; Yi Zhou; Yinghua Lu; Wenyao Shao (Advances in Polymer Technology)
Water flux is one of the most important performance parameters of the reverse osmosis (RO) membrane. The higher water flux means lower energy cost when treating the same volume of feed solution with membrane separation technology. However, the increase of membrane water flux always corresponds to the decrease of solvent rejection, known as the “trade-off” effect. In addition, the surface fouling of membranes is often a serious problem, as frequent cleaning not only increases the operating cost but also shortens the life of the membranes. Recently, various hydrophilic nanomaterials have been used to improve the performance of membranes. To fabricate thin film nanocomposite (TFN) RO membrane with high flux and antifouling performance, maleic anhydride-grafted graphene oxide (MG) was successfully synthesized and incorporated into the polyamide (PA) layer via the interfacial polymerization (IP) method. We performed the IP reaction with m-phenylenediamine (MPD) and trimesoyl chloride (TMC) as reactive monomers on a polysulfone (PSF) substrate, and acid absorbent (TEA) and surfactant (SDS) were added to improve the separation performance of the membrane. The effects of MG incorporation on the membrane morphology and separation performance were investigated. SEM and AFM results show that the surface of the MG membrane is rougher than that of the membrane without MG. In addition, excessive loading of MG will lead to aggregation of MG nanosheets. FT-IR spectra indicate that the interaction between MG and PA layers results in an increase of hydrophilic groups on the surface of the TFN membrane, which is further confirmed by the results of the contact angle. The optimal MG doping concentration in the aqueous solution is 0.004 wt%, the water flux of the resultant TFN membrane is significantly increased to 51 L·m-2·h-1, 150% higher than the blank control membrane, which also performs a higher NaCI rejection (97.5% vs. 96.6%). Furthermore, the MG-incorporated RO membrane exhibits superior antifouling performance compared with the blank control membrane.